SEM analysis on Global Fortune 500 Corporations with green ratings - García-Pina Rosete, Juan Carlos; Hernández Barros, Rafael; Blanco-Jiménez, Mónica (Energy Efficiency, 2021)
This paper aims to determine the relationships, if any, between the green ratings, deemed as eco-efficiency by employing a structural equations model (SEM) to determine the relationship between the Newsweek Green Rankings and the Global Fortune 500 Corporations. The methodology includes the analysis of four sustainability variables and four social responsibility variables evaluated in the Newsweek Green Rankings to study if there is a relationship between the implementation of such variables and the operational profitability performance and the possibility of the reduction of adverse risk effects in their continued operations. The objective of this paper is to provide empirical evidence that states the benefit of implementing eco-efficiency variables in their operations.
Keywords: sustainability; corporate social responsibility; green Rankings; risk; profit; JCR; Scopus